2010
DOI: 10.1093/jnci/djq125
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro and In Vivo Inhibition of Neuroblastoma Tumor Cell Growth by AKT Inhibitor Perifosine

Abstract: Perifosine inhibited the activation of AKT and was an effective cytotoxic agent in NB cells in vitro and in vivo. Our study supports the future clinical evaluation of perifosine for the treatment of NB tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 54 publications
8
59
0
Order By: Relevance
“…In support of our data, Perifosine, a pan Akt inhibitor, was recently shown to impair the growth of neuroblastoma cells in vitro and in vivo 31 . Although the family of PI3Ks is an attractive and promising target for small-molecule inhibitors in cancer therapy, toxicity associated with pan-selective inhibition of PI3Ks and Akt has been a major hurdle preventing the translation of this approach to patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In support of our data, Perifosine, a pan Akt inhibitor, was recently shown to impair the growth of neuroblastoma cells in vitro and in vivo 31 . Although the family of PI3Ks is an attractive and promising target for small-molecule inhibitors in cancer therapy, toxicity associated with pan-selective inhibition of PI3Ks and Akt has been a major hurdle preventing the translation of this approach to patients.…”
Section: Discussionsupporting
confidence: 89%
“…11,5 In neuroblastoma, studies have shown that inhibition of key molecules in the PI3K/Akt/mTOR signaling axis have profound effect on the survival of neuroblastoma cells. 5,6,14,22,31 Furthermore, inhibitors of PI3K/Akt or mTOR in combination with chemotherapeutic drugs use in neuroblastoma treatment often exhibit synergistic toxic effects on neuroblastoma cells in vitro.…”
mentioning
confidence: 99%
“…SMS-KCNR cells exhibit a uniform phenotype with small, round N-type cells that have short neuritic processes (34). This cell line was chosen as a model for mechanistic experiments in the current report since they display MYCN amplification, express caspase-8 (35) and apoptosis can be mediated through the intrinsic as well as extrinsic pathway (36). PAC-1A, however, induced cell death of SMS-KCNR through both apoptotic pathways via: i) modulation of expression of these mitochondrial Bcl-2 family proteins with pro-survival (Bcl-2, Bcl-xL) or pro-apoptotic (Bax, Bad, Bid) function, ii) TNF-family regulated extrinsic/death receptor signaling, and iii) activation of pro-apoptotic MAPK (e.g., SAPK/JNK) and suppression of pro-survival signaling through the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Perifosine exhibits antitumor activity by preventing Akt translocation to the cell membrane [114] . The drug has demonstrated antitumor effects in neuroblastoma, ovarian cancer, Waldenstrom's macroglobulinemia, medulloblastoma, kidney cancer, endometrial cancer, prostate cancer, myelogenous leukemia, multiple myeloma, squamous cell carcinoma, breast cancer, sarcoma, lung cancer, hepatocellular carcinoma, and other solid tumors [115][116][117][118][119][120][121][122][123][124][125][126][127] . With its success in preclinical models, Perifosine reached phase I and II trials for the treatment of only solid tumors, Waldenstrom's macroglobulinemia, and sarcoma [127][128][129] .…”
Section: Akt Inhibitorsmentioning
confidence: 99%